Pengaruh Perbedaan Aplikasi Pestisida pada Struktur Komunitas Mikroarthropoda Tanah dalam Skala Lapangan dan Laboratorium - Niswah, Rofiatun; Rahadian, Rully; Tarwotjo, Udi (Bioma : Berkala Ilmiah Biologi, 2019)
The choice of using pesticides with natural ingredients or synthetic chemicals is a differentiator between organic farming systems and inorganic farming systems. Pesticides are additives in agriculture to control pests or weeds. Abamectin is one of the active ingredients that can be found in pesticides. Ground microarthropods are members of the soil mesofauna, which are soil animals that have a body size ranging from 0.2-2 mm. The purpose of this study was to determine the effect of differences in the application of pesticides on a field or laboratory scale on the structure of soil microarthropod communities. Soil samples were taken from three agricultural lands, namely Bandungan inorganic agricultural land, Kopeng inorganic agricultural land and Kopeng organic agricultural land. The study was conducted in August to December 2018 in the Ecology and Biosystematic Laboratory of the Department of Biology, FSM Undip. Found a total of 60 species species richness originating from 13 orders. The application of pesticides which include the concentration and frequency of pesticide spraying has a negative influence on the structure of soil microarthopod communities. Application of abamectin pesticides on a laboratory scale proves that the administration of abamectin pesticides that exceeds the recommended concentration will adversely affect the structure of the soil microathropod community. Based on statistical tests of soil microarthropod species diversity from the results of the application of pesticides on a field and laboratory scale is significantly different.